Quality and Resilience of Subsidized Housing for Low-Income Communities in Disaster Prone Zone of Padang City: An Analysis of Residents' Perceptions - Syafri, Yuni Purnama; Furqani, Fahma; Octavia, Dyla Midya; Yunas, Barkhia; Zayu, Wiwin Putri (Applied Research in Science and Technology, 2025)
Background: Subsidized housing for Low-Income Communities (LIC) in Indonesia continues to encounter significant quality challenges, particularly in disaster-prone regions. These challenges are primarily associated with the limited enforcement of technical standards, insufficient infrastructure provision, and inadequate policy support, which collectively undermine the resilience and habitability of such housing.Aims and Methods: This study analyzes the quality and resilience of subsidized housing for LIC in Padang City, which are in disaster-prone zones. Using questionnaire survey methods and factor analysis, this study identified technical and non-technical variables that affect the feasibility of housing. The KMO-Bartlett test, validity, and reliability ensured the instrument's feasibility, resulting in 18 valid variables grouped into four main factors: the quality of infrastructure, facilities, and public utilities (IFP), housing development policies and support, technical quality and housing standards, and residential accessibility.Result: The study results show that basic infrastructure, regulatory support, implementation of technical standards, and strategic location have a significant role in the quality of subsidized housing. These findings confirm the importance of synergy between technical and policy aspects in improving the quality and resilience of subsidized housing, especially in disaster-risk areas.